The 3 C’s of Effective Department Leadership:Communication, Conflict, and Collegiality - Walt Gmelch (Academic Chairpersons Conference Proceedings, 2016)
Leading departments in institutions of higher education requires strategic executive skills. This workshop is a guide for those who want lead through effective communication practices, principled conflict resolution, and collegial department teamwork.
Keywords: Leading Departments in institutions